A case of prune belly syndrome: Experience from a regional hospital in Togo. (January 2023) - Essobiyou, Tamassi Bertrand; Kebalo, Sosso Piham; Pali, Essomondjona; Keheou, Alexandre Palissam; Issa, Mohamed; Dosseh, Ekoue David
Abstract: Introduction and importance: Prune Belly syndrome is a rare congenital condition first reported in 1939. It is a malformative disease associated with high mortality. We report a neonatal case in a regional hospital in Togo. Presentation of case: A 4-month-old male infant was brought to the hospital by his uncle because of a "deformity of the abdomen and absence of testicles". The examination revealed hypoplasia of the abdominal wall associated with bilateral cryptorchidism. Abdominal and urinary tract ultrasound revealed a left pyelocaliceal dilatation and a right megaureter. All these data allowed the diagnosis of Prune Belly syndrome. Conclusion: Prune Belly syndrome is a rare and complex disease with a high mortality rate. Highlights: Prune Belly syndrome is a rare malformative and congenital disease. The rarity of the disease causes a delay in diagnosis which is essentially clinical. The management of Prune Belly syndrome is multidisciplinary. In the African environment, this management is difficult due to the lack of qualified personnel.